Inhibitor-Immunology-Study - Wieland, I.; Wermes, C.; Eifrig, B.; Holstein, K.; Pollmann, H.; Siegmund, B.; Eberl, W.; Kemkes-Matthes, B.; Bidlingmaier, C.; Kurnik, K.; Lischetzki, G.; Nimtz-Talaska, A.; Eisert, R.; Bogdanova, N.; Doerk, T.; Sykora, K.-W. (Hämostaseologie, 2011)
The development of inhibitors in haemophilia B is one of the most important complications of replacement therapy, affecting mortality and morbidity. Inhibitor development is based on complex immunological factors, and to date, only little is known about its underlying mechanisms. Here, we present first results of the haemophilia B group of our Inhibitor-Immunology study.Patients, methods So far we have analysed 15 patients with haemophilia B. Four of them developed a high titre inhibitor; the remaining 11 had no inhibitor. We evaluated 9 SNPs in 8 genes (CD40, CTLA-4, IL-1β, IL-10, TLR2, TLR4, TLR9, TNF-α). We compared the distribution of these alleles between inhibitor and non-inhibitor haemophilia B patients and between haemophilia B patients and a normal male control population. HLA typing was performed in all patients.Results, discussion There appears to be a trend towards a skewed distribution of TLR 9, IL-10 and CTLA4 alleles in haemophilia B patients. Due to the limited number these differences are, however, not statistically significant.The t-test of all patients with inhibitor versus without inhibitor was significant for HLA-A*03 and DPB1*0401 and borderline for DRB1*0201.
Keywords: Haemophilia B; inhibitor; SNPs; HLA